2021
DOI: 10.3389/fbioe.2021.647874
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Quantitative Single Particle Characterization by Super Resolution Microscopy: From Virus Structures to Antivirals Design

Abstract: In the last year the COVID19 pandemic clearly illustrated the potential threat that viruses pose to our society. The characterization of viral structures and the identification of key proteins involved in each step of the cycle of infection are crucial to develop treatments. However, the small size of viruses, invisible under conventional fluorescence microscopy, make it difficult to study the organization of protein clusters within the viral particle. The applications of super-resolution microscopy have skyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 160 publications
(225 reference statements)
0
15
0
Order By: Relevance
“…While SRFM would ensure to visualize specific viral proteins with very high spatial resolution and practical compatibility with live-cell imaging [ 87 ], quite a few groups implemented it in the SARS-CoV-2 studies to date. Stebbing et al demonstrated that baricitinib, approved as a treatment for adult rheumatoid arthritis, can be a potential therapeutic through the inhibition of viral endocytosis or blockade of JAK1/2 kinase [ 88 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…While SRFM would ensure to visualize specific viral proteins with very high spatial resolution and practical compatibility with live-cell imaging [ 87 ], quite a few groups implemented it in the SARS-CoV-2 studies to date. Stebbing et al demonstrated that baricitinib, approved as a treatment for adult rheumatoid arthritis, can be a potential therapeutic through the inhibition of viral endocytosis or blockade of JAK1/2 kinase [ 88 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Two alternative single-particle microscopy methods that can be employed to study viral properties at the nanoscale are atomic force microscopy [ 2 ], which can be used to topographically scan the virus particle surface with a mechanical probe, or optical tweezers [ 3 ], a single-molecule technique that allows the measurement of forces between two samples or between the sample and the environment. Both of these methods have been used successfully to characterize viral systems [reviewed in [ 4 ]], however possess several limitations such as difficulty in identifying specific structures, slow scanning time, or problems in trapping nanostructures as large as viruses, which restricts their wide spread use.…”
Section: Introductionmentioning
confidence: 99%
“…The ground-breaking field of viral optical imaging, which includes studies of virus-host interactions, viral transmission, virus replication, assembly and budding, and the characterization of viral vaccines and anti-viral strategies, is continuously being updated with excellent reviews (for the latest contributions see [ 4 , [7] , [8] , [9] , [10] , [11] , [12] ]). This mini-review will focus on the application of SRM techniques to the elucidation of virus morphology and architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy has represented the method of choice for high-resolution imaging of virus structure since its introduction in the 1930s, but is comparatively low throughput, time consuming and offers limited molecular identification. To overcome those limitations and facilitate the highthroughput acquisition of images of filamentous influenza virions, we used direct stochastic optical reconstruction microscopy (dSTORM) 23 , a technique that allows the location of molecules to be determined with nanometer-scale precision at a resolution of less than 20 nm and offers an exciting alternative for virus imaging 24,25 . This method is compatible with immunostaining, allowing us to specifically label viral proteins within virions.…”
Section: Introductionmentioning
confidence: 99%